1997
DOI: 10.1103/physrevb.55.6309
|View full text |Cite
|
Sign up to set email alerts
|

Fracton excitation and Lévy flight dynamics in alkali silicate glasses

Abstract: We have examined the relaxation behavior of alkali metal ions in lithium metasilicate glasses by means of molecular dynamics simulation. We have observed a change of slope of the mean squared displacement at ϳ300 ps. In shorter time regions, localized motion of lithium ions within neighboring sites is observed, which is caused by the small fracton dimension ͑fracton excitation͒. On the other hand, an accelerated motion of particles due to cooperative jumps is found, which characterizes the diffusion and conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
66
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 15 publications
(19 reference statements)
10
66
0
Order By: Relevance
“…The cage decay is slow in the time regime of tӶ m , and therefore gives rise to a nearly frequency independent loss for the frequency range ӷ1/ m . Such a qualitative description of the NCL has support from molecular-dynamics simulations 37,38 from the time evolution of the van Hove function at times before the ions leave their cages, where the mean-square displacement was found to increase very slowly with log(t), consistent with NCL. Such a time dependent mean-square displacement will give rise to the NCL through the relation between the frequency dependence of conductivity and the time dependence of mean-square displacement; 39…”
Section: Resultsmentioning
confidence: 80%
“…The cage decay is slow in the time regime of tӶ m , and therefore gives rise to a nearly frequency independent loss for the frequency range ӷ1/ m . Such a qualitative description of the NCL has support from molecular-dynamics simulations 37,38 from the time evolution of the van Hove function at times before the ions leave their cages, where the mean-square displacement was found to increase very slowly with log(t), consistent with NCL. Such a time dependent mean-square displacement will give rise to the NCL through the relation between the frequency dependence of conductivity and the time dependence of mean-square displacement; 39…”
Section: Resultsmentioning
confidence: 80%
“…27 Jumping ions with forward correlation related with the power law distribution of effective jump length (Lévy flight 28 ) are found to be the main component contributing diffusive motion at longer time scales 29 and they reduce the values of dw2. 13 A relation between cooperative jumps and successive jumps had been pointed out before 29 and the deterministic character of such motions was clarified later. 30 Similar motions called "stringlike" motions are also found in other glass forming liquids.…”
Section: Fractal Dimension Of the Random Walksmentioning
confidence: 99%
“…In investigations of the nature of transport in glassy systems and, in particular, in silicate glasses, Hiwatari and collaborators [37][38][39][40] showed that diffusion is facilitated not through single jump motions, but through forward correlated jumps, which require cooperative motions of two or more particles. In this kind of motion one particle occupies the position of another particle, which in turn moves simultaneously forward to another previously occupied site and so forth.…”
Section: ͑10͒mentioning
confidence: 99%